Effect of the addition of bee pollen to the diet on performance, eggshell quality and serum parameters in layer quails - OLGUN, O; YILDIZ, AÖ; ŞENTÜRK, ET; ABDULQADER, AF (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was carried out to determine the effect of bee pollen addition to quail diets on performance, eggshell quality and serum biochemical properties. In the experiment, 120 quails aged 70 days were randomly distributed to 6 treatment groups with 4 replicates. The quails were fed for 10 weeks with 6 trial diets with 0, 2, 4, 6, 8 and 10 g/kg bee pollen added. The body weight change, egg production, egg weight, egg mass, feed conversion ratio, damaged eggs, eggshell weight, eggshell thickness and serum glucose, creatinine, albumin, globulin and total protein levels of quails were not affected by the addition of bee pollen to the diet (P>0.05). The addition of 10 g/kg bee pollen to the diet significantly decreased feed intake compared to the control group (0 g/kg). Eggshell breaking strength was decreased by adding bee pollen to the diet and the lowest value was observed at the group fed the diet containing 6 g/kg bee pollen.Serum cholesterol concentration was minimized when 10 g/kg bee pollen was added to the diet(P<0.05). In addition, serum calcium and phosphorus contents were increased compared to the control (0 g/kg) group and these parameters reached the maximum at the 10 g/kg bee pollen level (P<0.01).According to the results of the experiment, the addition of bee pollen to the diet had a positive effect on serum cholesterol, calcium and phosphorus levels in layer quails, however, it had a negative effect on eggshell breaking strength.